Implementasi Firewall Untuk Keamanan Dan Pencegahan Serangan Siber Di SMAI Kepanjen Kabupaten Malang - Yuri Ariyanto; Yan Watequlis Syaifudin; Budi Harijanto; Chandrasena Setiadi; M Hasyim Ratsanjani; Hendra Pradibta; Ali Ridho Muladawila; Didik Sunariyanto (P3M Politeknik Negeri Malang, 2025)
The implementation of a firewall-based network security system has become increasingly important in maintaining data integrity and availability within educational institutions. The Community Service Program (PPM) conducted by Politeknik Negeri Malang aims to enhance the network security infrastructure at SMA Islam Kepanjen, Malang Regency, through the implementation of Wazuh as a cybersecurity solution. This approach includes the installation and configuration of network infrastructure, security audits, and training for IT staff on independent firewall management. The implementation methodology involves site surveys, network topology design, hardware and software installation, system testing, and technical mentoring. The outcomes achieved include increased awareness of cybersecurity issues and improved capacity of partner personnel in managing the network infrastructure. With the implementation of Wazuh, it is expected that SMA Islam Kepanjen will be able to proactively address cyber threats and serve as a model for information technology implementation in other schools across Malang Regency.